CLEC16A variants conferred a decreased risk to allergic rhinitis in the Chinese population - Niu, Yongliang; Wang, Haiying; Li, Zhengqing; Shamsi, Bilal Haider; Liu, Mingxia; Liu, Juan; Wang, Qiang; Liu, Yonglin (Frontiers in Genetics, 2022)
Background: Allergic rhinitis (AR) is a chronic respiratory disease. Hereditary factors played a key role in the pathogenesis of the AR. This study investigated the association between CLEC16A variants and AR risk in the Chinese population. Methods: We applied Agena MassARRAY technology platform to genotype five single nucleotide polymorphisms (SNPs) located in CLEC16A in 1004 controls and 995 cases. The association between CLEC16A SNPs (rs2286973, rs887864, rs12935657, rs11645657 and rs36045143) and AR risk were calculated by logistic regression analysis, with odds ratio (OR) and 95% confidence interval (CI). False-positive report probability (FPRP) was also used to assess the significant results to reduce false positives. Multifactor dimensionality reduction (MDR) was completed to assess the interaction between CLEC16A variants to predict AR risk. Results: Totally, CLEC16A (rs887864, rs12935657, rs2286973, rs11645657 and rs36045143) were significantly associated with AR risk. Therein, rs2286973, rs11645657 and rs36045143 were related to a decreased risk of AR in the people ≤43 years old, females and the people with BMI≤24, respectively. And rs887864 and rs12935657 were also associated with a decreased susceptibility of AR in the people ＞43 years old. Meanwhile, in the results of region stratification, rs887864 conferred a reduced risk to AR in the people from loess hilly area. Conclusions: CLEC16A variants conferred a decreased risk to AR in the Chinese population.